2010
DOI: 10.1126/science.1193420
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of a Population of Submillimeter-Bright, Strongly Lensed Galaxies

Abstract: Gravitational lensing is a powerful astrophysical and cosmological probe and is particularly valuable at submillimeter wavelengths for the study of the statistical and individual properties of dusty star-forming galaxies. However, the identification of gravitational lenses is often time-intensive, involving the sifting of large volumes of imaging or spectroscopic data to find few candidates. We used early data from the Herschel Astrophysical Terahertz Large Area Survey to demonstrate that wide-area submillimet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
502
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(531 citation statements)
references
References 42 publications
27
502
2
Order By: Relevance
“…The selection is especially easy since the lensed sources are the brightest sources in the submm maps, and only basic spectral filtering for radio-bright blazars is needed to find the lensed DSFGs in millimeter maps. Negrello et al (2010) demonstrated through multi-wavelength follow-up observations of the first five Herschel-selected DSFGs with S 500 > 100 mJy at 500µm, after accounting for nearby spiral galaxies and radio-bright blazars, are all gravitationally lensed (Fig. 34).…”
Section: Lensed Dsfgsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection is especially easy since the lensed sources are the brightest sources in the submm maps, and only basic spectral filtering for radio-bright blazars is needed to find the lensed DSFGs in millimeter maps. Negrello et al (2010) demonstrated through multi-wavelength follow-up observations of the first five Herschel-selected DSFGs with S 500 > 100 mJy at 500µm, after accounting for nearby spiral galaxies and radio-bright blazars, are all gravitationally lensed (Fig. 34).…”
Section: Lensed Dsfgsmentioning
confidence: 99%
“…In this context, gravitational lensing has played a critical role because the spatial enhancement associated with magnification provides a way to investigate the internal structure of distant, faint galaxies to levels unattainable with the current generation of instrumentation for typical DSFGs. A second important fact here is that large samples of gravitationally lensed galaxies can be efficiently selected by searching for bright sources in wide area submillimeter surveys (Blain, 1996;Perrotta et al, 2002;Negrello et al, 2007Negrello et al, , 2010Hezaveh & Holder, 2011;Wardlow et al, 2013). While the early submm surveys were limited to smaller sky areas, the advent of wide-field surveys, especially with Herschel and SPT, at sub/millimeter wavelengths have allowed detections of large samples of lensed DSFGs that can be followed up with a host of radio and submm/mm-wave interferometers.…”
Section: Detailed Studies Of Individual Dusty Star-forming Galaxiesmentioning
confidence: 99%
“…Now, Herschel (Pilbratt et al 2010) has found that lensing is significant for some of the brightest submm sources, with surveys such as H-ATLAS and HerMES (Herschel Multi-tiered Extragalactic Survey) turning up a population of sources which are boosted enough that they can be studied in great detail in follow-up observations (e.g. Negrello et al 2010;Wardlow et al 2013). How-E-mail: todd@phas.ubc.ca ever, the limited resolution of Herschel, and of non-interferometric ground-based observatories such as the JCMT, means that the effects of source blending are a cause of uncertainty in interpreting the results (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is true that a significant fraction of IRAS hyperluminous infrared galaxies are lensed (Rowan-Robinson & Wang 2010 estimate the lensed percentage to be 10-30%). Negrello et al (2010) show 5 lensed galaxies from the Herschel-Atlas survey. They estimate that a significant fraction (50%?)…”
Section: Submillimetre Galaxiesmentioning
confidence: 99%